Blue light perovskite thin film, preparation method thereof and blue light perovskite light emitting diode
Patent Information
- Application Number
- CN202311824179.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-26
AI Technical Summary
然而,采用氯离子和溴离子混合制备的蓝光钙钛矿,其在电场作用下容易发生卤素离子迁移而造成相分离,进而导致光谱随电压变化,严重影响蓝光钙钛矿发光二极管的光谱稳定性
[0020]Based on the above technical solution, the blue perovskite thin film and its preparation method, and the blue perovskite light-emitting diode provided in this disclosure have at least one of the following beneficial effects:
Smart Images

Figure CN117946673B_ABST
Abstract
Description
Technical Field
[0001] This disclosure belongs to the field of electroluminescent materials and device fabrication technology, and particularly relates to a blue perovskite thin film and its preparation method, and a blue perovskite light-emitting diode. Background Technology
[0002] In recent years, metal halide perovskite materials have been considered a promising emerging semiconductor light-emitting material due to their unique optoelectronic properties, such as high conductivity, narrow emission spectrum, high carrier mobility, high fluorescence quantum yield, continuously tunable emission spectrum, low-temperature solution processing capability, large-area fabrication capability, and low cost. They have already been successfully applied in light-emitting diodes (PeLEDs). Perovskite LEDs can effectively overcome the shortcomings of both inorganic and organic light-emitting diodes (LEDs), and have enormous application potential in flat panel displays and solid-state lighting.
[0003] In the field of perovskite light-emitting diodes (LEDs), red and green LEDs have achieved external quantum efficiency (EQE) exceeding 20%, with corresponding breakthroughs in stability. This indicates a promising future for perovskite LEDs in both display and lighting applications. However, blue perovskite LEDs, as a core component of full-color displays and white lighting, lag behind red and green perovskite LEDs in both performance and stability. Currently, the highest EQE for blue perovskite LEDs is only 10%. Therefore, further research and breakthroughs are needed for highly efficient and stable blue perovskite LEDs.
[0004] Mixing halide ions (mainly a mixture of bromide and chloride ions) and constructing a quasi-two-dimensional perovskite structure with pure bromide ions are currently the two main strategies for adjusting the band gap of perovskite materials to achieve a blue shift in light color. However, blue light perovskites prepared by mixing chloride and bromide ions are prone to halide ion migration and phase separation under an electric field, leading to spectral variations with voltage and severely affecting the spectral stability of blue light perovskite LEDs. Secondly, although introducing sterically hindered organic ligands can construct a quasi-two-dimensional perovskite structure with pure bromide ions, achieving blue light emission from a low-dimensional phase with a wide band gap, controlling the phase distribution in the quasi-two-dimensional perovskite is very difficult, easily resulting in the coexistence of perovskite phases with different n values. Moreover, the energy transfer from the low-dimensional phase to the high-dimensional phase is relatively inefficient, making it difficult for blue light perovskite LEDs to achieve high-efficiency blue light emission.
[0005] Therefore, there is an urgent need to develop a blue light perovskite thin film, a blue light perovskite light-emitting diode, and their fabrication methods to solve the problems of low luminous efficiency, unstable spectrum, and short lifespan of current blue light perovskite light-emitting diodes, and ultimately achieve effective and stable emission in the blue light range. Summary of the Invention
[0006] To address the aforementioned technical problems, this disclosure provides a blue perovskite thin film and its preparation method, as well as a blue perovskite light-emitting diode, aiming to solve the technical problems of low luminous efficiency, unstable spectrum, and short lifespan of blue perovskite light-emitting diodes.
[0007] To solve the above-mentioned technical problems, the technical solution provided in this disclosure is as follows:
[0008] As a first aspect of this disclosure, a blue light-emitting perovskite thin film is provided, comprising: a mixed halide ion perovskite, an organic ligand, and an organic stabilizer.
[0009] The mixed halide perovskite is formed by the reaction of cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, and formamidinium hydrobromide, with the organic ligand being the substituted aryl alkylamine salt derivative Y-Ph-C. m H 2m-1 NH3 + X1 - The organic stabilizer is selected from any one of the following:
[0010]
[0011] Where Y is an electron-withdrawing group, Ph is a phenylene group, m is an integer from 1 to 6, and X1 and X2 are halogens.
[0012] As a second aspect of this disclosure, a method for preparing a blue light perovskite thin film is provided, comprising:
[0013] Cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and organic ligands are dissolved in an organic solvent to obtain a precursor solution;
[0014] An organic stabilizer was added to the precursor solution to obtain a perovskite precursor solution;
[0015] Under an inert atmosphere, a perovskite precursor solution was spin-coated onto a substrate to obtain a nascent thin film.
[0016] After the nascent film is heated and annealed, a blue perovskite film is obtained.
[0017] As a third aspect of this disclosure, a blue perovskite light-emitting diode is provided, comprising:
[0018] An anode substrate and a cathode, and a hole transport layer, a modification layer, a light-emitting layer, an electron transport layer and an electron injection layer are sequentially disposed from the anode substrate to the cathode.
[0019] The light-emitting layer is the aforementioned blue light perovskite film, and the thickness of the blue light perovskite film is 5-100 nm.
[0020] Based on the above technical solution, the blue perovskite thin film and its preparation method, and the blue perovskite light-emitting diode provided in this disclosure have at least one of the following beneficial effects:
[0021] (1) In the embodiments of this disclosure, the addition of organic ligands with certain steric hindrance to the perovskite will prevent the original three-dimensional perovskite lattice from being effectively maintained, and the lattice will separate along the organic ligands with certain steric hindrance, thereby forming a quasi-two-dimensional perovskite. Although the addition of organic ligands can achieve blue light emission of the low-dimensional phase with a wide band gap, it is easy to produce perovskite phase distributions with different n values (n=2 or n=3, where n is the number of layers of the perovskite inorganic framework). To this end, this disclosure introduces organic stabilizers. Because the structure of organic stabilizers contains atoms with high electron cloud density (such as N and P), they can form hydrogen bonds with hydrogen atoms on the amino groups of the organic ligands. These hydrogen bonds can weaken the activity of the organic ligands, weaken the interaction between the organic ligands and the perovskite crystals, inhibit the formation of the low-dimensional phase in the perovskite, and gradually transform into a high-dimensional phase, thereby reducing the energy loss in the perovskite film caused by insufficient energy transfer.
[0022] (2) In the embodiments of this disclosure, the organic stabilizer can increase the exciton binding energy of the blue perovskite and suppress the exciton energy loss caused by exciton-phonon coupling. The electrostatic and coordination interactions formed between the organic stabilizer and lead ions in the mixed halide ion perovskite can suppress halide ion migration in the perovskite, significantly improving the spectral stability of the blue perovskite light-emitting diode. Furthermore, the coordination interaction can delay the excessively rapid growth of the perovskite during crystallization, increase the crystallinity of the perovskite, passivate defect sites in the perovskite, reduce defects in the perovskite, and lower radiative recombination transitions, thereby giving the blue perovskite light-emitting diode higher luminous efficiency, spectral stability, and lifetime. Attached Figure Description
[0023] Figure 1 This is a high-resolution scanning transmission electron microscope image of the perovskite light-emitting diodes fabricated in the embodiments of this disclosure.
[0024] Figure 2 This is an external quantum efficiency-luminance curve of the perovskite light-emitting diode prepared in Example 1 of this disclosure when the mass concentration of the organic stabilizer is 4 wt%.
[0025] Figure 3 The electroluminescence spectra of the perovskite light-emitting diode prepared in Example 1 of this disclosure with an organic stabilizer mass concentration of 4 wt% at different voltages are shown.
[0026] Figure 4 The electroluminescence spectra of the perovskite light-emitting diode in Comparative Example 2 of this disclosure at different voltages are shown.
[0027] Figure 5 The operating stability graph measured at 100 cd m -2 The operating stability graph measured at 100 cd m
[0028] Figure 6 The phase distribution graph in the perovskite of the blue perovskite light-emitting diode in the present disclosure embodiment 1, embodiment 16-17 and comparative example 2 without organic stabilizer;
[0029] Figure 7 The electroluminescence spectrum graph of the blue perovskite light-emitting diode with different Cl - / Br - The electroluminescence spectrum graph of the blue perovskite light-emitting diode with different Cl
[0030] Figure 8 The peak external quantum efficiency statistical graph of the blue perovskite light-emitting diode in the present disclosure embodiment 1 and embodiment 18-19 and various blue perovskite light-emitting diodes reported. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical scheme and advantages of the present disclosure more clear, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the drawings.
[0032] At present, with the rapid development of perovskite light-emitting diodes, the relatively backward efficiency and stability of blue light (especially deep blue light) perovskite light-emitting diodes have restricted the further application of perovskite light-emitting diodes in the field of display and lighting. In order to solve the problems of low luminous efficiency, unstable spectrum and short service life of blue light perovskite light-emitting diodes, the present disclosure proposes a blue light perovskite thin film and a preparation method thereof, and a blue light perovskite light-emitting diode. By introducing an organic stabilizer and an organic ligand with large steric hindrance in the process of preparing the blue light perovskite thin film, the two-dimensional perovskite phase distribution is regulated to inhibit the formation of low-dimensional phases (n = 2 and n = 3) in the perovskite thin film and increase the content of quasi-three-dimensional phases (n ≥ 4) in the perovskite thin film. In addition, because the energy transfer from the low-dimensional phase to the high-dimensional phase is inefficient, the method of the present disclosure is used to prepare the blue light perovskite thin film, which can reduce the energy loss caused by insufficient energy transfer in the perovskite thin film. The use of an organic stabilizer increases the exciton binding energy of a blue light perovskite, inhibits the exciton energy loss caused by exciton-phonon coupling, and the electrostatic and coordination effects between the organic stabilizer and the perovskite can effectively inhibit the migration of halogen ions in the perovskite, thereby significantly improving the luminous efficiency, spectral stability and service life of the blue light perovskite light-emitting diode.
[0033] Specifically, as a first aspect of the present disclosure, a blue light perovskite thin film is provided, comprising: a mixed halide ion perovskite, an organic ligand, and an organic stabilizer, wherein the mixed halide ion perovskite is formed by a reaction of cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidine hydrobromide, the organic ligand is a substituted aryl alkyl amine salt derivative Y-Ph-C m H2 m-1 NH3 + X1 - The organic stabilizer is selected from any one of the following: wherein Y is an electron-withdrawing group, Ph is a phenylene group, m is an integer of 1-6, and X1 and X2 are halogens.
[0034] In embodiments of the present disclosure, the addition of an organic ligand with a certain steric hindrance to the perovskite will make the original three-dimensional perovskite lattice unable to be effectively maintained, and will separate along the organic ligand with a certain steric hindrance, thereby forming a quasi-two-dimensional perovskite. Although this can achieve low-dimensional phase blue light emission with a wider band gap, it is easy to produce perovskite phase distribution with different n values. To this end, by introducing an organic stabilizer, because the structure of the organic stabilizer contains atoms with a larger electron cloud density, a hydrogen bond can be formed with the hydrogen atom on the amino group in the organic ligand. This hydrogen bond can weaken the activity of the organic ligand, weaken the action of the organic ligand and the perovskite crystal, inhibit the formation of low-dimensional phase in the perovskite, and gradually change to form a high-dimensional phase, thereby reducing the energy loss caused by insufficient energy transfer in the perovskite thin film. In addition, the use of an organic stabilizer can increase the exciton binding energy of the blue light perovskite and inhibit the exciton energy loss caused by exciton-phonon coupling. The electrostatic interaction and coordination action between the organic stabilizer and the lead ion in the perovskite can inhibit the migration of halide ions in the perovskite, significantly improve the spectral stability of the blue light perovskite light-emitting diode. In addition, the coordination action can delay the too fast growth of the perovskite during the perovskite crystallization process, improve the crystallinity of the perovskite, passivate the unsaturated sites in the perovskite, reduce the defects in the perovskite, and reduce the radiative recombination transition, thereby realizing a blue light perovskite light-emitting diode with high luminous efficiency, spectral stability, and lifetime.
[0035] According to embodiments of the present disclosure, the organic ligand is a substituted alkyl amine salt derivative Y-Ph-C m H2 m-1 NH3, wherein C + X1 - , and X2 are selected from Cl, Br, or I. m H2 m-1 Preferably, X1 is Br, and X2 is selected from Cl, Br, or I.
[0036] According to embodiments of the present disclosure, the organic ligand is a substituted alkyl amide salt derivative Y-Ph-C
[0037]
[0038] Further, the organic ligand is selected from any one of the following specific structures:
[0039]
[0040]
[0041] According to an embodiment of the present disclosure, the organic stabilizer is selected from any one of the following specific structures:
[0042]
[0043] As a second aspect of the present disclosure, a method for preparing the above-mentioned blue light perovskite thin film is provided, comprising: dissolving cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidine hydrobromide and an organic ligand in an organic solvent to obtain a precursor solution; adding an organic stabilizer to the precursor solution to obtain a perovskite precursor solution; under an inert atmosphere, spin coating the perovskite precursor solution onto a substrate to obtain a nascent thin film; and after the nascent thin film is subjected to a heating annealing treatment, a blue light perovskite thin film is obtained.
[0044] In an embodiment of the present disclosure, the organic ligand and the organic stabilizer are added in the process of preparing the perovskite precursor solution, and the organic ligand and the organic stabilizer are used to form hydrogen bonds, which can adjust the phase distribution of the blue light perovskite, effectively inhibit the formation of low-dimensional phases (n = 2 and n = 3), and increase the content of high-dimensional phases (n ≥ 4) in the blue light perovskite thin film, so that the excitons can be effectively transferred to the high-dimensional phases through an energy funneling process, reduce the energy loss caused by insufficient energy transfer in the perovskite thin film, and ultimately improve the light-emitting efficiency of the blue light perovskite thin film.
[0045] According to an embodiment of the present disclosure, the molar ratio of cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidine hydrobromide and the organic ligand is 1:(0.1-1):(0.1-1):(0.01-0.5):(0.01-0.5):(0.01-0.2):(0.01-2), and is preferably 1:0.5:0.5:0.05:0.3:0.05:0.8; the concentration of cesium ions is 0.1-0.2 mol / L; the molar ratio of lead chloride to lead bromide is 1-3:1-3, and the molar ratio of lead chloride to lead bromide is preferably 1:1. The mass concentration of the organic stabilizer in the precursor solution is 1wt%-10wt%, and is preferably 4wt%. The organic solvent is at least one of dimethyl sulfoxide (DMSO) and N,N-dimethylformamide (DMF), and the organic solvent is preferably dimethyl sulfoxide.
[0046] According to embodiments of this disclosure, the rotational speed of the perovskite precursor solution spin-coating onto the substrate is 3000-8000 rpm, preferably 4500 rpm; the total spin-coating time is 30-180 seconds, preferably 120 seconds; the substrate is selected from any one of ITO conductive glass, glass, quartz, silicon substrate, and flexible substrate, preferably ITO conductive glass.
[0047] According to embodiments of this disclosure, the annealing temperature for the nascent thin film is 50–100°C, preferably 75°C; the annealing time is 1–20 minutes, preferably 5 minutes. It should be noted that both the spin-coating of the perovskite precursor solution onto the substrate and the annealing of the nascent thin film are performed under an inert gas atmosphere, wherein the inert gas can be nitrogen.
[0048] For example, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and a sterically hindered organic ligand are mixed in a ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 and dissolved in an organic solvent of DMSO to obtain a precursor solution. A 2 wt% organic stabilizer is added to the precursor solution to obtain a perovskite precursor solution. In a nitrogen-filled glove box, the perovskite precursor solution is coated onto a substrate (ITO conductive glass) to obtain a nascent thin film. The nascent thin film is then annealed at 75°C for 5 minutes under a nitrogen atmosphere to obtain a blue perovskite thin film.
[0049] As a third aspect of this disclosure, a blue perovskite light-emitting diode is provided, comprising: an anode substrate and a cathode, and a hole transport layer, a modification layer, a light-emitting layer, an electron transport layer and an electron injection layer sequentially disposed from the anode substrate to the cathode; wherein the light-emitting layer is the blue perovskite thin film in the above embodiments, and the thickness of the blue perovskite thin film is 5-100 nm.
[0050] This disclosure also provides a method for fabricating a blue perovskite light-emitting diode, comprising:
[0051] Step 1: The anode substrate is ultrasonically cleaned sequentially with deionized water, acetone and ethanol, and then subjected to plasma treatment.
[0052] Step 2: On the plasma-treated anode substrate, a hole transport layer, a modification layer, and a light-emitting layer are sequentially prepared by spin coating.
[0053] Step 3: On the perovskite light-emitting layer, an electron transport layer, an electron injection layer, and a cathode are sequentially prepared by vacuum evaporation.
[0054] According to embodiments of this disclosure, the materials selected for each layer in the fabrication of the blue perovskite light-emitting diode are as follows:
[0055] The anode material is a transparent conductive material, including metal, metal oxide conductive glass, or flexible transparent electrode, and is generally disposed on a substrate. The substrate is selected from any one of glass, quartz, silicon substrate, or flexible substrate, with glass being preferred. Examples of anode materials include indium tin oxide (ITO) conductive films, doped with zinc tin dioxide or indium gallium zinc oxide, with indium tin oxide (ITO) being the preferred anode material. Processing methods for forming the conductive material (anode) on the substrate include, but are not limited to, sputtering, chemical vapor deposition, and spray high-temperature decomposition lamps. The thickness of the formed anode is 10-300 nm, preferably 150 nm.
[0056] The hole transport layer is a compound with high mobility that matches the emitting layer (blue light perovskite film) and the anode energy level, including but not limited to one or more of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT:PSS), polyvinylcarbazole (PVK), poly[((9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(p-butylphenyl))-diphenylamine)] (TFB), poly(N,N'-bis-4-butylphenyl-N,N'-bisphenyl)benzidine (Poly-TPD), poly[bis(4-phenyl)(2,4,7-trimethylphenyl)amine] (PTAA), and nickel oxide (NiOx), wherein the hole transport layer is preferably polyvinylcarbazole (PVK). The thickness of the hole transport layer formed on the anode substrate by spin coating is 10-100 nm, preferably 10 nm.
[0057] The material of the modification layer is selected from one or more of polyethyleneimine (PEI), polyethoxyethyleneimine (PEIE), polyethylene (PVA), polyethylene oxide (PEO), polyethylene glycol (PEG), modified polyethylene glycol (mPEG), and polyvinylpyrrolidone (PVP), wherein the modification layer is preferably poly(4-vinylpyridine) (PVP). The thickness of the modification layer formed on the hole transport layer by spin coating is 1-10 nm, preferably 5 nm.
[0058] The light-emitting layer is the blue perovskite thin film in the above embodiments, and the thickness of the light-emitting layer (Perovskite) is 5-100nm, preferably 20nm.
[0059] The electron transport layer is a compound with high mobility that matches the energy levels of the electron injection layer and the emitting layer, including but not limited to one or more of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi), (1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene)(POT2T), (2,4,6-tris[3-(diphenylphosphino)phenyl]-1,3,5-triazole)(4,6-bis(3,5-di(3-pyridinyl)phenyl)-2-methylpyrimidine)(TmPyPB), and zinc oxide (ZnO). The electron transport layer is preferably 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi). The thickness of the electron transport layer formed on the emitting layer by vacuum evaporation is 20-100 nm, preferably 50 nm.
[0060] The electron injection layer is a compound with high mobility that matches the electron transport layer and the cathode level, including but not limited to one or more of lithium fluoride (LiF), 8-hydroxyquinoline-lithium (Liq), and alkali metals, wherein the electron injection layer is preferably 8-hydroxyquinoline-lithium (Liq). The thickness of the electron injection layer formed on the electron transport layer by vacuum evaporation is 0.5-10 nm, preferably 2 nm.
[0061] The cathode material is selected from one or more of aluminum, silver, gold, and magnesium, with aluminum (Al) being the preferred cathode. The thickness of the cathode is 50-200 nm, preferably 100 nm.
[0062] Specifically, in step 1, the anode substrate (ITO conductive glass) is ultrasonically cleaned for 30 minutes in sequence with detergent, deionized water, acetone and ethanol, dried and then treated with oxygen plasma for 5 minutes to further remove organic matter on the anode substrate and form a certain roughness on its surface for subsequent spin coating.
[0063] In step 2, polyvinylcarbazole (PVK) was dissolved in chlorobenzene at a concentration of 6 mg / mL. The completely dissolved solution was then filtered through a 0.2 μm PTFE filter and spin-coated onto an ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain the hole transport layer. Poly(4-vinylpyridine) (PVP) was dissolved in isopropanol at a concentration of 2 mg / mL and then spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain the modification layer. The prepared perovskite precursor solution was spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain the luminescent layer (perovskite blue light film).
[0064] In step 3, at 4×10-4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) is sequentially deposited on the light-emitting layer by vacuum evaporation. Then, an electron injection layer of lithium 8-hydroxyquinoline (Liq) is deposited on the electron transport layer, and a cathode of aluminum (Al) is deposited on the electron injection layer, thereby obtaining the target blue perovskite light-emitting diode.
[0065] Therefore, the blue perovskite light-emitting diode prepared by the above method comprises, from the anode substrate to the cathode (from bottom to top): a 150 nm glass substrate with an ITO (indium tin oxide) conductive film, a 10 nm PVK hole transport layer, a 5 nm PVP modification layer, a 20 nm perovskite light-emitting layer, a 50 nm TPBi electron transport layer, a 2 nm Liq electron injection layer, and a 100 nm Al cathode. A high-resolution scanning transmission electron microscope (STEM) image of the perovskite light-emitting diode prepared by the above method is shown below. Figure 1 As shown.
[0066] The following detailed description, in conjunction with specific embodiments and accompanying drawings, illustrates the above-mentioned blue perovskite thin film, blue perovskite light-emitting diode, and their fabrication method. However, the following embodiments are merely illustrative of the technical solutions disclosed herein, and the scope of protection of this disclosure is not limited thereto.
[0067] Example 1: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-1 and organic stabilizer 2-1-1
[0068] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and sterically hindered organic ligand 1-1-1 were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was then deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer to obtain the target perovskite light-emitting diode device. In Example 1, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0069] The external quantum efficiency (EQE)-current density characteristic curves and electroluminescence (EL) spectra of the blue perovskite light-emitting diodes prepared by the method in Example 1 were tested, and the specific test results are shown in Table 1.
[0070] Figure 2 This is an external quantum efficiency-luminance curve of the perovskite light-emitting diode prepared in Example 1 of this disclosure when the organic stabilizer mass concentration is 4wt%.
[0071] like Figure 2 As shown, tests revealed that when the mass concentration of the organic stabilizer was 4wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2A maximum EQE of 21.4% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 21.4%. -2 At the desired brightness, it still maintains an EQE of over 15%, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 1 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 125 min. The perovskite device fabricated using the method in Example 1 exhibits superior peak external quantum efficiency compared to previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED). Figure 8 (As shown).
[0072] Example 2: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-2 and organic stabilizer 2-1-1
[0073] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-2 with a certain occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 2, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0074] The perovskite light-emitting diodes prepared using the method in Example 2 were subjected to external quantum efficiency (EQE)-current density characteristic curves and electroluminescence (EL) spectra. The specific test results are shown in Table 1.
[0075] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the fabricated blue perovskite light-emitting diode device exhibited a performance of 22 cd / m². -2 A maximum EQE of 19.5% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 19.5%. -2 At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite LED devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 2 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 101 min. The perovskite device prepared by the method in Example 2 has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0076] Example 3: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-3 and organic stabilizer 2-1-1
[0077] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-3 with a certain directional hindrance were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 3, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0078] The perovskite light-emitting diodes prepared using the method in Example 3 were subjected to external quantum efficiency (EQE)-current density characteristic curves and electroluminescence (EL) spectra. The specific test results are shown in Table 1.
[0079] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 19.0% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 19.0%. -2At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite LED devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 3 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 99 min. The blue perovskite light-emitting diode prepared by the method in Example 3 has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot (QDLED) light-emitting diodes.
[0080] Example 4: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-5 and organic stabilizer 2-1-1
[0081] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-5 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite emitting layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 4, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0082] The perovskite light-emitting diodes prepared using the method in Example 4 were subjected to external quantum efficiency (EQE)-current density characteristic curves and electroluminescence (EL) spectra. The specific test results are shown in Table 1.
[0083] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 18.7% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 18.7%. -2 At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite LED devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 4 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 98 min. The perovskite device prepared by the method in Example 4 has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0084] Example 5: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-6 and organic stabilizer 2-1-1
[0085] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-6 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 5, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0086] The perovskite light-emitting diodes prepared using the method in Example 5 were subjected to external quantum efficiency (EQE)-current density characteristic curves and electroluminescence (EL) spectra. The specific test results are shown in Table 1.
[0087] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 18.3% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 18.3%. -2 At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite LED devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 5 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 95 minutes. The perovskite device prepared by the method in Example 5 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0088] Example 6: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-7 and organic stabilizer 2-1-1
[0089] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-7 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 6, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0090] The perovskite light-emitting diodes prepared using the method in Example 6 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0091] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 17.5% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 17.5%. -2At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite LED devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 6 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 89 minutes. The perovskite device prepared by the method in Example 6 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0092] Example 7: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-8 and organic stabilizer 2-1-1
[0093] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-8 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 7, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0094] The perovskite light-emitting diodes prepared using the method in Example 7 were subjected to external quantum efficiency (EQE)-current density characteristic curves and electroluminescence (EL) spectra. The specific test results are shown in Table 1.
[0095] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 17.3% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 17.3%. -2 At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite light-emitting diode devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite light-emitting diode in Example 7 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 85 minutes. The perovskite device prepared by the method in Example 7 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0096] Example 8: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-9 and organic stabilizer 2-1-1
[0097] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes each, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-9 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 8, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0098] The perovskite light-emitting diodes prepared using the method in Example 8 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0099] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 18.3% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 18.3%. -2 At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite light-emitting diode devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite light-emitting diode in Example 8 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 93 min. The perovskite device prepared by the method in Example 8 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0100] Example 9: Preparation of Blue Perovskite Light Emitting Diodes using Organic Ligand 1-1-1 and Organic Stabilizer 2-2-1
[0101] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, and other additives were added. Zinc chloride aqueous solution, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-1 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-2-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite emitting layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 9, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0102] The perovskite light-emitting diodes prepared using the method in Example 9 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectroscopy tests. The test results are shown in Table 1.
[0103] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 19.6% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 19.6%. -2At the specified brightness, it still maintains an EQE of over 15%, which is a significant improvement compared to blue perovskite light-emitting diode devices without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite light-emitting diode in Example 9 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 98 minutes. The perovskite device prepared by the method in Example 9 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0104] Example 10: Preparation of Blue Perovskite Light Emitting Diodes using Organic Ligand 1-1-9 and Organic Stabilizer 2-2-1
[0105] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, and other additives were added. Zinc chloride aqueous solution, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-9 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-2-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue-light perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 10, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0106] The perovskite light-emitting diodes prepared using the method in Example 10 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0107] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 17.6% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 17.6%. -2 It maintains an EQE of over 15% even at low brightness, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 10 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 85 minutes. The perovskite device prepared by the method in Example 10 has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED), and quantum dot light-emitting diodes (QDLED).
[0108] Example 11: Preparation of blue perovskite light-emitting diodes using organic ligand 1-1-1 and organic stabilizer 2-3-1
[0109] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, and other additives were added. Zinc chloride aqueous solution, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-1 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-3-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite emitting layer. Finally, a 4×10⁻⁶ layer was formed. -4Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 11, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0110] The perovskite light-emitting diodes prepared using the method in Example 11 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectra, and the results are shown in Table 1.
[0111] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 A maximum EQE of 18.1% was achieved at a brightness level of up to 250 cd / m². Furthermore, this blue perovskite LED achieved a maximum EQE of 18.1%. -2 It maintains an EQE of over 15% even at low brightness, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 11 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 87 min. The perovskite device prepared by the method in Example 11 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED) and quantum dot light-emitting diodes (QDLED).
[0112] Example 12: Preparation of Blue Perovskite Light Emitting Diodes using Organic Ligand 1-1-9 and Organic Stabilizer 2-3-1
[0113] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, and other additives were added. Zinc chloride aqueous solution, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-1-9 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-3-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite emitting layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 12, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0114] The perovskite light-emitting diodes prepared using the method in Example 12 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0115] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 It achieves a maximum EQE of 17.0% at high brightness. Meanwhile, this blue perovskite LED achieves a maximum EQE of 17.0% at a brightness of up to 250 cdm. -2It maintains an EQE of over 15% even at low brightness, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 12 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 83 min. The perovskite device prepared by the method in Example 12 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED) and quantum dot light-emitting diodes (QDLED).
[0116] Example 13: Preparation of blue perovskite light-emitting diodes using organic ligand 1-2-1 and organic stabilizer 2-1-1
[0117] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, and other additives were added. Zinc chloride aqueous solution, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-2-1 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite emitting layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 13, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0118] The perovskite light-emitting diodes prepared using the method in Example 13 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0119] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 It achieves a maximum EQE of 20.1% at high brightness. Meanwhile, this blue perovskite LED achieves a maximum EQE of 20.1% at a brightness of up to 250 cdm. -2 It maintains an EQE of over 15% even at low brightness, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 13 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 105 min. The perovskite device prepared by the method in Example 13 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED) and quantum dot light-emitting diodes (QDLED).
[0120] Example 14: Preparation of Blue Perovskite Light Emitting Diodes using Organic Ligand 1-3-1 and Organic Stabilizer 2-1-1
[0121] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, lead chloride, and other additives were added. Zinc chloride aqueous solution, lithium bromide, formamidinium hydrobromide, and an organic ligand 1-3-1 with a specific occlusion were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 14, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0122] The perovskite light-emitting diodes prepared using the method in Example 14 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0123] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 At a maximum brightness level, it achieves a maximum EQE of 19.8%. Simultaneously, this blue perovskite LED achieves a brightness of up to 250 cdm. -2 It maintains an EQE of over 15% even at low brightness, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 14 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 97 min. The perovskite device prepared by the method in Example 14 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED) and quantum dot light-emitting diodes (QDLED).
[0124] Example 15: Preparation of Blue Perovskite Light Emitting Diodes using Organic Ligand 1-4-1 and Organic Stabilizer 2-1-1
[0125] A glass substrate with an ITO conductive film was ultrasonically cleaned sequentially with detergent, deionized water, acetone, and ethanol for 30 minutes, dried, and then treated with oxygen plasma for 5 minutes. A solution of poly(N-vinylcarbazole) (PVK) dissolved in chlorobenzene at a concentration of 6 mg / mL was filtered through a 0.2 μm PTFE filter and spin-coated onto the ITO substrate at 5000 rpm for 35 seconds, followed by annealing at 100°C for 15 minutes to obtain a hole injection layer. A solution of poly(4-vinylpyridine) (PVP) dissolved in isopropanol at a concentration of 2 mg / mL was spin-coated onto the hole injection layer at 5000 rpm for 20 seconds, followed by annealing at 100°C for 15 minutes to obtain a modification layer. Subsequently, cesium bromide, lead bromide, and lead chloride were added. Anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and sterically hindered organic ligand 1-4-1 were dissolved in dimethyl sulfoxide (DMSO) in a molar ratio of 1:0.5:0.5:0.05:0.3:0.05:0.8 to obtain a precursor solution. Organic stabilizer 2-1-1 was added to the precursor solution to obtain a perovskite precursor solution with an organic stabilizer concentration of 4 wt%. This solution was then spin-coated onto a PVK / PVP substrate at 4500 rpm for 120 seconds and annealed at 75°C for 5 minutes to obtain a blue perovskite luminescent layer. Finally, a 4×10⁻⁶ layer was formed. -4 Under pressure of Pa, an electron transport layer of 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene (TPBi) was deposited on the light-emitting layer using vacuum evaporation. An electron injection layer of lithium 8-hydroxyquinoline (Liq) was deposited on the electron transport layer, and an aluminum cathode (Al) was deposited on the electron injection layer, thereby obtaining the target perovskite light-emitting diode device. In Example 15, the perovskite light-emitting diode device had an anode thickness of 150 nm, a hole transport layer thickness of 10 nm, a modification layer thickness of 5 nm, a light-emitting layer thickness of 20 nm, an electron transport layer thickness of 50 nm, an electron injection layer thickness of 2 nm, and a cathode thickness of 100 nm.
[0126] The perovskite light-emitting diodes prepared using the method in Example 15 were subjected to EQE-current density characteristic curves and electroluminescence (EL) spectral tests. The specific test results are shown in Table 1.
[0127] Testing revealed that, ultimately, when the organic stabilizer concentration was 4 wt%, the blue perovskite light-emitting diode device achieved a performance of 22 cd / m². -2 It achieves a maximum EQE of 19.5% at high brightness. Meanwhile, this blue perovskite LED achieves a brightness of up to 250 cdm. -2It maintains an EQE of over 15% even at low brightness, representing a significant improvement compared to blue perovskite LEDs without high steric hindrance organic ligands and organic stabilizers. Furthermore, the blue perovskite LED in Example 15 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The peak external quantum efficiency can reach 93 min. The perovskite device prepared by the method in Example 15 above has a higher peak external quantum efficiency than previously reported perovskite (PeLED), organic (OLED) and quantum dot light-emitting diodes (QDLED).
[0128] Example 16
[0129] The preparation method of the blue perovskite light-emitting diode in Example 16 is the same as that in Example 1, the only difference being that the mass concentration of the doped organic stabilizer is 2wt%.
[0130] Example 17:
[0131] The preparation method of the blue perovskite light-emitting diode in Example 17 is the same as that in Example 1, the only difference being that the mass concentration of the doped organic stabilizer is 8 wt%.
[0132] Example 18:
[0133] The preparation method of the blue perovskite light-emitting diode in Example 18 is the same as that in Example 1, except that the molar ratio of PbCl2:PbBr2 is 3:2.
[0134] Example 19:
[0135] The preparation method of the blue perovskite light-emitting diode in Example 19 is the same as that in Example 1, except that the molar ratio of PbCl2:PbBr2 is 2:1.
[0136] Comparative Example 1:
[0137] The fabrication method of the blue perovskite light-emitting diode in Comparative Example 1 is the same as that of the perovskite light-emitting diode in Example 1. The only difference is that no organic ligand with a certain tack resistance is used in the light-emitting layer of the perovskite light-emitting diode.
[0138] Comparative Example 2:
[0139] The perovskite light-emitting diode in Comparative Example 2 was prepared using the same method as that in Example 1, except that no organic stabilizer was used in the light-emitting layer of the perovskite light-emitting diode.
[0140] Comparative Example 3:
[0141] The perovskite light-emitting diode in Comparative Example 3 was prepared using the same method as that in Example 1, except that no organic ligands or organic stabilizers with a certain locating resistance were used in the light-emitting layer of the perovskite light-emitting diode.
[0142] The specific structures of the compounds involved in the above embodiments are as follows:
[0143]
[0144] The current-luminance-voltage characteristics of the perovskite light-emitting diode devices doped with organic ligands and organic stabilizers in the corresponding embodiments were obtained using a Keithley source measurement system (Keithley 2400 Sourcemeter, Keithley 2000 Currentmeter) with a calibrated silicon photodiode. Electroluminescence spectra were measured using a Photo Research PR655 spectrometer. The external quantum efficiency of the blue perovskite light-emitting diode devices was calculated using the method described in Adv. Mater., 2003, 15, 1043-1048. A summary of the performance of the perovskite light-emitting diode devices in the above embodiments and the comparative examples is shown in Table 1.
[0145] Table 1. Performance of blue perovskite light-emitting diode devices in the examples and comparative examples.
[0146]
[0147] The lifetime of the perovskite light-emitting diode is [value missing] at an initial brightness of 100 cd / m². -2 The following measurements were taken: the concentration of the organic stabilizer was its mass concentration in the perovskite precursor solution; the PbCl2 / PbBr2 molar ratio was its molar ratio in the perovskite precursor solution.
[0148] Figure 3 The electroluminescence spectra of the perovskite light-emitting diode prepared in Example 1 of this disclosure with an organic stabilizer mass concentration of 4 wt% at different voltages are shown. Figure 4 The electroluminescence spectra of the perovskite light-emitting diode in Comparative Example 2 of this disclosure at different voltages are shown. Figure 5 The perovskite light-emitting diode prepared in Example 1 of this disclosure with an organic stabilizer concentration of 4 wt% and the perovskite light-emitting diode in Comparative Example 2 have a similar performance at 100 cd / m². -2 Operational stability diagram measured under brightness conditions.
[0149] Compared to perovskite light-emitting layers without sterically hindered organic ligands (Comparative Example 1), or light-emitting layers without organic stabilizers (Comparative Example 2), and light-emitting layers without both sterically hindered organic ligands and organic stabilizers (Comparative Example 3), this disclosure achieves efficient and stable fabrication of blue perovskite thin films and blue perovskite light-emitting diodes by utilizing the aforementioned organic ligands and organic stabilizers with specific steric hindrance. These diodes can achieve narrowband blue light emission of 483 nm with a brightness of 22 cd / m² at the optimal organic stabilizer doping concentration. -2 The peak EQE can reach 21.4%, while at 250 cd m -2 It can still achieve a high efficiency of 15% at low brightness, making it a superior blue perovskite light-emitting diode currently available. Specifically, the blue perovskite light-emitting diode in Example 1 achieves an initial brightness of 100 cd / m². -2 Under irradiation, device lifetime T 50 The luminous efficiency can reach 125 min, and the stability is 30 times higher than other blue perovskite LEDs. The reason for this is likely that organic stabilizers were added during the preparation of the blue perovskite thin film, increasing the exciton binding energy of the blue perovskite and suppressing exciton energy loss caused by strong exciton-phonon coupling. In addition, the organic stabilizers and lead ions in the perovskite can form electrostatic and coordination interactions, effectively suppressing halide ion migration in the perovskite, thus ultimately achieving a significant improvement in the luminous efficiency, spectral stability, and lifetime of the blue perovskite LED (e.g., ...). Figure 3 , 4, 5).
[0150] Figure 6 The diagram shows the phase distribution of the blue perovskite light-emitting diodes in Embodiments 1 and 16-17 of this disclosure and the perovskite without organic stabilizer in Comparative Example 2.
[0151] like Figure 6As shown, in the perovskite thin film, the low-dimensional phase with n=2 exhibits a peak at 425 nm, n=3 at 450 nm, and n≥4 at 478 nm. It can be seen from the figure that Comparative Example 2 (containing only organic ligands) and Example 16 (organic stabilizer concentration of 2 wt%) both have phases with n=2 and n=3. However, for Example 1 (organic stabilizer concentration of 4 wt%) and Example 17 (organic stabilizer concentration of 8 wt%), only one peak is observed at 478 nm. Therefore, it can be seen from Examples 1 and 16-17 that as the concentration of organic stabilizer doping gradually increases, the peaks at n=2 and n=3 gradually disappear and gradually transform into a peak at 478 nm for n≥4, indicating that the low-dimensional phase gradually transforms into a high-dimensional phase. This demonstrates that, compared to the light-emitting layer without organic stabilizers (Comparative Example 2), the present disclosure introduces organic ligands and organic stabilizers with certain steric hindrance during the preparation of the perovskite light-emitting layer. The hydrogen bonding between the two can regulate the phase distribution of the blue light perovskite, that is, suppress the formation of low-dimensional phases (n=2 and n=3) in the perovskite film, increase the composition of quasi-three-dimensional phases (n≥4) in the perovskite film, and reduce the energy loss in the perovskite film due to insufficient energy transfer.
[0152] Further research was conducted on the fabrication and performance improvement of deep blue perovskite light-emitting diodes, such as... Figure 7 As shown. Specifically, in this embodiment of the invention, deep blue light emission can also be achieved by adjusting the chloride ion content in the perovskite precursor solution.
[0153] Figure 7 The different Cl in Embodiment 1 and Embodiments 18-19 of this disclosure - / Br - Electroluminescence spectrum of blue perovskite light-emitting diodes with ratios.
[0154] like Figure 7 As shown, when the molar ratio of PbCl2 / PbBr2 is 1:1, the electroluminescence peak is located at 483 nm, and the EQE can reach 21.4%; when the molar ratio of PbCl2 / PbBr2 is 3:2, the electroluminescence peak is located at 473 nm, the EQE can reach 13.2%, and the CIE value is (0.124, 0.090); when the molar ratio of PbCl2 / PbBr2 is 2:1, the electroluminescence peak is located at 464 nm, the EQE can reach 7.3%, and the CIE value is (0.148, 0.048).
[0155] Figure 8 The peak external quantum efficiency statistics of the blue perovskite light-emitting diodes in Embodiments 1 and 18-19 of this disclosure are compared with those of various previously reported blue perovskite light-emitting diodes.
[0156] like Figure 8As shown, the external dot efficiency of the perovskite light-emitting diode device prepared by the above method is superior to that of previously reported perovskite (PeLED), organic (OLED) and quantum dot light-emitting diodes (QDLED).
[0157] The specific embodiments described above further illustrate the purpose, technical solutions, and beneficial effects of this disclosure. It should be understood that the above descriptions are merely specific embodiments of this disclosure and are not intended to limit this disclosure. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the protection scope of this disclosure.
Claims
1. A blue light perovskite thin film, comprising: Mixed halide perovskite, organic ligands, and organic stabilizers The mixed halide ion perovskite is formed by the reaction of cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, and formamidinium hydrobromide, and the organic ligand is a substituted aryl alkylamine salt derivative Y-Ph-C. m H 2m-1 NH3 + X1 - The organic stabilizer is selected from any one of the following: 、 、 , Wherein, Y is an electron-withdrawing group, Ph is a phenylene group, and C... m H 2m-1 It is a straight-chain alkyl group, m is an integer from 1 to 6, X1 and X2 are halogens, and the electron-withdrawing group is selected from any one of the following: 、 、 、 、 、 、 、 、 ; The blue light perovskite film is obtained by spin-coating a perovskite precursor solution, which is formed by a precursor solution and an organic stabilizer, onto a substrate under an inert atmosphere and then undergoing a heating annealing treatment. The phase distribution of the blue light perovskite film is adjusted by forming hydrogen bonds between the organic ligand and the organic stabilizer, thereby achieving the transformation from a low-dimensional phase to a high-dimensional phase and the disappearance of the low-dimensional phase. The low-dimensional phase is n=2 and n=3, and the high-dimensional phase is n≥4, where n represents the number of layers of the perovskite inorganic framework. In the precursor solution, the molar ratio of cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and organic ligand is 1:(0.1~1):(0.1~1):(0.01~0.5):(0.01~0.5):(0.01~0.2):(0.01~2), the concentration of cesium ions is 0.1~0.2 mol / L, and the molar ratio of lead chloride to lead bromide is 1:
1. The organic stabilizer accounts for 4 wt% of the perovskite precursor solution.
2. The blue light perovskite thin film according to claim 1, wherein: X1 is Br, and X2 is selected from Cl, Br or I.
3. The blue light perovskite thin film according to claim 1, wherein, The organic ligand is selected from any one of the following: 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 、 。 4. The blue light perovskite thin film according to claim 1, wherein, The organic stabilizer is selected from any one of the following: 、 、 、 、 、 、 、 、 。 5. A method for preparing a blue light perovskite thin film as described in any one of claims 1-4, comprising: Cesium bromide, lead bromide, lead chloride, anhydrous zinc chloride, lithium bromide, formamidinium hydrobromide, and organic ligands are dissolved in an organic solvent to obtain a precursor solution; An organic stabilizer was added to the precursor solution to obtain a perovskite precursor solution. Under an inert atmosphere, the perovskite precursor solution is spin-coated onto a substrate to obtain a nascent thin film. The nascent film is then subjected to a heat annealing treatment to obtain the blue light perovskite film. The organic ligand and the organic stabilizer are as defined in any one of claims 1-4.
6. The method according to claim 5, wherein: The organic solvent is at least one of dimethyl sulfoxide and N,N-dimethylformamide; The rotation speed for spin coating the perovskite precursor solution onto the substrate is 3000~8000 rpm, and the total spin coating time is 30~180 seconds. The temperature for annealing the nascent film is 50~100℃, and the annealing time is 1~20 minutes.
7. A blue perovskite light-emitting diode, comprising: An anode substrate and a cathode, and a hole transport layer, a modification layer, a light-emitting layer, an electron transport layer and an electron injection layer are sequentially disposed from the anode substrate to the cathode. Wherein, the light-emitting layer is the blue light perovskite thin film according to any one of claims 1-4, and the thickness of the blue light perovskite thin film is 5-100 nm.